Improved black hole and multiverse algorithms for discrete sizing optimization of planar structures. Issue 10 (3rd October 2019) - Gholizadeh, Saeed; Razavi, Navid; Shojaei, Emad
ABSTRACT: This study compares two novel nature-inspired algorithms developed based on cosmology for discrete sizing optimization of structures. The first metaheuristic is the black hole, which is inspired by the black hole phenomenon. The second one is the multiverse, and the main inspiration for this algorithm is based on three concepts in cosmology: white holes, black holes and wormholes. Moreover, an improved version of each algorithm, termed improved black hole (IBH) and improved multiverse (IMV), is proposed to overcome the defects of their original versions in tackling the discrete sizing structural optimization problems. Three types of structure, i.e. steel trusses, steel frames and reinforced concrete frames, are presented to illustrate the efficiency of the proposed IBH and IMV algorithms. The numerical results demonstrate the excellence of the proposed improved algorithms compared with other state-of-the-art metaheuristics in the literature, in terms of their optimum solutions and reliability.